2022
DOI: 10.3390/su14105884
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Energy Potential from Coffee Pulp in a Hydrothermal Power Market through System Dynamics: The Case of Colombia

Abstract: Colombia has abundant solar, wind, and biomass resources for energy production with non-conventional renewable energy (NCREs) sources. However, the current participation of NCREs is negligible in the electricity mix of the country, which has historically depended on hydroelectric plants. Meteorological phenomena, such as the El Niño–Southern Oscillation (ENSO), threaten the energy supply during periods of drought, and the generation of energy using fossil fuels is necessary to offset the hydric deficit. Since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The oceans cover more than 70% of Earth's energy. In them you can find two types of energy: thermal that comes from solar heating and mechanical from tides and waves (Martínez- Ruiz et al, 2022). The sun warms the surface of the oceans in a very high proportion, compared to the deep areas, in this way it creates a difference in temperatures that can also be exploited, but is insecure due to the phenomena to which the oceans are subject.…”
Section: Energy From the Oceansmentioning
confidence: 99%
“…The oceans cover more than 70% of Earth's energy. In them you can find two types of energy: thermal that comes from solar heating and mechanical from tides and waves (Martínez- Ruiz et al, 2022). The sun warms the surface of the oceans in a very high proportion, compared to the deep areas, in this way it creates a difference in temperatures that can also be exploited, but is insecure due to the phenomena to which the oceans are subject.…”
Section: Energy From the Oceansmentioning
confidence: 99%
“…Previous research has identified some of these potential streams. The potential of coffee waste to produce energy has previously been simulated using system dynamics [7]. In 2020, a study of the potential for converting around 8.7 tons of coffee waste to added-value products such as briquettes was undertaken [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the specific case of Colombia, which is a country widely known as a producer of coffee and, to a lesser extent, sugar, rice, cotton, corn, and shrimp, the waste generated in these agroindustries could be used to obtain this type of polymeric material. For example, in the case of coffee, this industry only uses the grain, which is equivalent to 5% of the fruit, leaving 95% waste, where approximately 60% of this is cellulose [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%